STUDI DRUG UTILIZATION REVIEW (DUR) TERHADAP PENGGUNAAN ANTIBIOTIK PADA INFEKSI SALURAN PERNAPASAN ATAS - Fajar Amirulah (Universitas 17 Agustus 1945 Jakarta, 2026)
Upper respiratory tract infection (URTI) is a condition characterized by irritation and swelling of the upper respiratory tract without pneumonia, usually accompanied by a cough. According to the Indonesian Ministry of Health, the use of medication can be categorized as rational when the medication given meets the patient's needs. Treatment can only be considered rational if it meets several criteria, namely: the right patient, the right indication, the right drug, the right dose, the right interval of administration, the right duration of administration, and others. The objective of this study is to examine the use of antibiotics for ARI in pediatric patients at Jawilan Health Center. The research method employed is a descriptive method with a cross-sectional design to determine the pattern of antibiotic use for ARI in pediatric patients. Data collection was conducted retrospectively using secondary data obtained from medical records and prescriptions of patients with ARI during the period of May 2024–April 2025 at Puskesmas Jawilan, Serang Regency, Banten. The number of patients was 261 patients aged 1-17 years, diagnosed with ARI and given antibiotics. The most commonly used class of antibiotics was amoxicillin, with 253 administrations (96.9%), followed by cotrimoxazole with 8 administrations (3.1%). The results of the treatment rationality are as follows: correct patient 100%, correct indication 77%, correct drug 100%, correct dosage 86.6%, correct interval of antibiotic administration 100%, and correct duration of antibiotic administration 97.7%. From this research data, it can be concluded that there are still irrational drug administrations below 100% that have long-term effects on the patient's body.